Motivating consumers for health and fitness: The role of app features - Stancu, Violeta; Frank, Darius‐Aurel; Lähteenmäki, Liisa; Grunert, Klaus G. (Journal of consumer behaviour, 2022)
Smartphone apps can create value for consumers by supporting their health goals. The purpose of the study was to reveal people's preferences for Self‐Determination theory derived app features of health‐related apps that can potentially promote motivation and sustained use of such apps. Three discrete choice experiments, followed by a ranking task, were used to assess consumer preferences for specific app features that can support the basic needs for autonomy, competence and relatedness among respondents from Germany and Spain (N = 719). Participants preferred the autonomy supporting app features, namely making changes to the menu recommendations or self‐selecting their rewards. The competence supporting features of levels of progress and feedback that provided encouragement together with facts were preferred across countries; however, presenting the feedback in a dynamic display was disliked in Germany. The relatedness supporting feature, presence of an anthropomorphic cue with the menu recommendations, was preferred in Germany but disliked in Spain. Health and fitness apps can benefit from including features that bring value to consumers by responding to their psychological needs and help them achieve their health goals. Allowing choice flexibility in app recommendations, providing feedback that is encouraging in addition to informative, and including gamification elements in health apps, can respond to consumer preferences and thereby increase engagement with apps. The study contributes to understanding how the theoretically derived features of health apps can be included in the design of apps to match consumer preferences.